Socio-emotional development in high functioning children with autism spectrum disorders using a humanoid robot - Soares, Filomena (2019)
The use of robots had already been proven to encourage the promotion of social interaction and skills lacking in children with Autism Spectrum Disorders (ASD), who typically have difficulties in recognizing facial expressions and emotions. The main goal of this research is to study the influence of a humanoid robot to develop socio-emotional skills in children with ASD. The children’s performance in game scenarios aiming to develop facial expressions recognition skills is presented. Along the sessions, children who performed the game scenarios with the robot and the experimenter had a significantly better performance than the children who performed the game scenarios without the robot. The main conclusions of this research support that a humanoid robot is a useful tool to develop socio-emotional skills in the intervention of children with ASD, due to the engagement and positive learning outcome observed.